“Petits pas. Nulle part. Obstinément”: Writing Finitude, Writing On - Mihálycsa, Erika (Hungarian Journal of English and American Studies, 2020)
Review essay:Craig, George, Martha Dow Fehsenfeld, Dan Gunn, and Lois More Overbeck, eds. The Letters of Samuel Beckett. Volume IV: 1966-1989. Cambridge: CUP, 2016. cvii + 838 pages. ISBN 978-0-521-867962. £ 30.